2009
DOI: 10.1097/ccm.0b013e3181962d39
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-hemorrhagic shock-induced red blood cell damage leads to decreased microcirculatory blood flow*

Abstract: T/HS induces significant changes in RBC functions and the injection of T/HS, but not T/SS, RBC leads to decreased organ blood flow. These findings confirm the hypothesis that T/HS-induced RBC alterations will directly cause organ hypoperfusion and suggest that T/HS-induced RBC damage contributes to this process. Thus, T/HS-induced changes in RBC function may contribute to the development of shock-induced multiple organ failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 29 publications
4
34
0
2
Order By: Relevance
“…24 In several studies and in different types of shock, the presence of microcirculatory dysfunction has been associated with poor outcomes, including a higher frequency of organ failure and mortality. 14,15,25,26 In our small series of patients, the microcirculation was moderately to severely compromised, in line with previous studies of patients with severe sepsis and septic shock. 14,22,23 For example, Creteur et al 22 reported NIRS ascending slope values of 2.3 ± 1.3%Ásec -1 in patients with septic shock, a value similar to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…24 In several studies and in different types of shock, the presence of microcirculatory dysfunction has been associated with poor outcomes, including a higher frequency of organ failure and mortality. 14,15,25,26 In our small series of patients, the microcirculation was moderately to severely compromised, in line with previous studies of patients with severe sepsis and septic shock. 14,22,23 For example, Creteur et al 22 reported NIRS ascending slope values of 2.3 ± 1.3%Ásec -1 in patients with septic shock, a value similar to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…It should be stated that in these two aforementioned experiments, abnormal RBCs were produced in-vitro but not as a result of a real critical condition. The conclusions received in these two studies were confirmed in "pure" in-vivo experiments by Machiedo et al [18]. The authors performed exchange transfusion in rats with blood obtained animals rats subjected to trauma-hemorrhagic shock or to sham shock.…”
supporting
confidence: 67%
“…The morphological changes and damage that occur to RBCs after hemorrhagic trauma may impair their function and ability to traverse the microcirculation, which, in turn, could potentially lead to reduced microvascular blood flow and increased tissue hypoxia [60,61]. Membrane signals displayed by the damaged RBCs-such as oxidized proteins and lipids, exposure of phosphatidylserine, clustering of RBC structural proteins, and binding sites for free hemoglobin and complement-target the RBCs for clearance by the reticuloendothelial system [52,[62][63][64][65][66].…”
Section: The Intersection and Parallels Of Trauma Pathobiology And Rbmentioning
confidence: 99%